2021
DOI: 10.1021/acs.organomet.1c00218
|View full text |Cite
|
Sign up to set email alerts
|

Two-Coordinate Iron(I) Complexes on the Edge of Stability: Influence of Dispersion and Steric Effects

Abstract: Sequential treatment of Fe­[N­(SiMe3)­DIPP]2 (2) with Et3NHCl, IAd, and KC8 (IAd = 1,3-diadamantyl-imidazolin-2-ylidene, DIPP = 2,6-diisopropylphenyl) results in the formation of two new complexes, (IAd)­Fe­[N­(SiMe3)­DIPP]2 (3) and {(IAd)­Fe­[N­(SiMe3)­DIPP]}2(μ-N2) (4), via disproportionation and N2 trapping of the intermediate species (IAd)­Fe­[N­(SiMe3)­DIPP] (A), respectively. Independent syntheses of complexes 3 and 4 were also developed. These results differ from those observed with the IPr-supported an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Unfortunately, as shown by H 2 in Figure 1 (and many other species), chemical bond formation/cleavage can be without energy barriers. Additionally, energy based metrics can be affected by nonbonding interactions like dispersion, which may constitute a large proportion of the interaction energy [26,27] …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, as shown by H 2 in Figure 1 (and many other species), chemical bond formation/cleavage can be without energy barriers. Additionally, energy based metrics can be affected by nonbonding interactions like dispersion, which may constitute a large proportion of the interaction energy [26,27] …”
Section: Figurementioning
confidence: 99%
“…Additionally, energy based metrics can be affected by nonbonding interactions like dispersion, which may constitute a large proportion of the interaction energy. [26,27] An alternative is to focus on the end of electron sharing. Homolytic cleavage in closed-shell molecules results in the separation of bonded electron pairs into independent radical fragments.…”
mentioning
confidence: 99%
“…Complexes with two-coordinate, open-shell 3d-metal­(I) ions, known for chromium to nickel, are a particular class of compounds in coordination chemistry. They show interesting single molecule magnetic properties, and can be used for bond activation, which has focused so far on the metals iron, cobalt, ,, and especially nickel. In contrast, the chemistry of two-coordinate chromium­(I) is considerably less developed. This is remarkable as the linear chromium­(I) complex [TerCr­(PMe 3 )] (Ter = 2,6-Tripp 2 -3,5- i Pr 2 -C 6 H, Tripp = 2,4,6- i Pr 2 -C 6 H 2 ) was the very first example within this class of molecules (Figure A) .…”
Section: Introductionmentioning
confidence: 99%
“…[14] While the chemistry of this iron amide has been significantly less explored than that of its HMDS congener, it has been found to undergo reduction using KC 8 furnishing potassium Fe(I) ferrate species [15,16] or NHC-stabilized heteroleptic two-coordinate Fe(I) complexes. [17,18] The latter complexes can effectively catalyse cyclotrimerisations of terminal and internal alkynes. [17,19] Recent studies by our group and others have shown that combining iron(II) amides (or alkyls) with a group 1 metal reagent lead to the formation of bimetallic bases (via cocomplexation) capable of promoting FeÀ H exchange reactions of different aromatic substrates.…”
Section: Introductionmentioning
confidence: 99%